Elucidation of the Relationship between Peri-Implantitis and Fluoride: A Correlation Study - Chikazu, Daichi; Yamakawa, Daiki; Murata, Takuya; Kohinata, Daichi; Takahasi, Hidetosi; Kawase-Koga, Yoko (Journal of Hard Tissue Biology, 2021)
Fluoride has recently been indicated as a risk factor for peri-implantitis. However, no reports have confirmed this intraorally in humans or in experiments using large animals. Thus, in the present study, we used beagles to verify the effects on surrounding tissue when dental implants were implanted and peri-implantitis was induced. To elucidate any possible correlation with peri-implantitis, we also quantitatively examined titanium corrosion and elution due to fluoride. subjects were divided into three groups, namely, (1) no fluoride, no pressure thread; (2) fluoride, no pressure thread; and (3) fluoride, pressure thread. All the total 12 implants survived, indicating an implant survival rate of 100%. Dental X-ray measurement of bone resorption and measurement of bone destruction volume with μCT indicated significantly more bone resorption and bone destruction in group (3) than in group (1). There was no significant difference between group (1) and group (2). in addition, there was no significant difference between group (2) and group (3). Scanning electron microscope measurement of titanium in gingiva around the implants did not reveal any significant differences among the three groups. Based on quantitative data, our results suggested that fluoride exacerbates peri-implantitis.